Developing students' civic responsibility using blended learning model with an asynchronous system - Cahyono, Cahyono; Danial, Endang; Rahmat, Rahmat; Masyitoh, Iim Siti; Romli, Asep Darojatul (Universitas Negeri Yogyakarta, 2024)
The development of technology and the world of education today requires complex thinking. Technology can be used to make the learning process easier, more interesting, and more enjoyable. However, learning must continue to focus on the elements of competency achievement that must be achieved and the humanist element. The blended learning model with synchronous and asynchronous systems is one model that can be used in today's technology-based learning era, especially asynchronous systems. This study aims to determine the effectiveness of asynchronous learning in increasing the students' civic responsibility at one of the universities in Bandung City. Experiments in research are considered more appropriate for answering the research objectives. The research subjects were students of the environmental engineering study program (experimental class) and food engineering study program (control class). The results showed that asynchronous learning was more effective for increasing students' civic responsibility, with an average post-test score of 91.50.